2020
DOI: 10.1111/apa.15340
|View full text |Cite
|
Sign up to set email alerts
|

Children’s exposure to psychological abuse and neglect: A population‐based study in rural Bangladesh

Abstract: Child psychological abuse is a pattern of caregiver's intentional or unintentional behaviour towards the child that convey to a child that s/he is worthless, flawed, unloved, unwanted, endangered or only of value to meet another's needs, while neglect is caretaker's failure to meet the child's basic physical and psychological needs. 1 Several studies reveal a diverse picture of child psychological abuse and neglect across countries and cultures. 2,3 In a meta-analytical study, global prevalence of child psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 26 publications
(60 reference statements)
4
25
2
Order By: Relevance
“…However, in some previous studies, higher rates of child PA (95%), PsyA (97%) and neglect (70%) were reported among normally developed children in Bangladesh [6,7]. So, the prevalence of different types of maltreatment reported in the present study is not exceptionally high than previous studies' findings in children without disabilities.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, in some previous studies, higher rates of child PA (95%), PsyA (97%) and neglect (70%) were reported among normally developed children in Bangladesh [6,7]. So, the prevalence of different types of maltreatment reported in the present study is not exceptionally high than previous studies' findings in children without disabilities.…”
Section: Discussioncontrasting
confidence: 79%
“…Studies from Bangladesh revealed almost all rural children aged 11-17 years, irrespective of their physical and mental conditions, faced at least one form of physical abuse (PA) or psychological abuse (PsyA) in the past year 6,7 . Although studies revealed that CM is highly prevalent in Bangladesh, there is no study regarding the prevalence of CM among children with ASD 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…1 This is evident in the article by Haque et al in this issue of Acta Paediatrica, which demonstrates that nearly all children interviewed in the study had experienced some form of psychological abuse and a majority had been exposed to neglect. 2 Previous research by the same group showed similar findings regarding child physical abuse. Chronic or long-term stress erodes the fabric of empathy and tolerance and lowers the threshold for abuse and neglect.…”
Section: Daunting But Not Impossible-addressing Child Maltreatment Insupporting
confidence: 52%
“…Younger age at marriage was associated with increased domestic violence (from a partner or other family member),69 and with IPV 52 70–73. An association between the village-level prevalence of child marriage (<15 years) and IPV was found in Bangladesh, suggesting that women who lived in villages with high levels of child marriage were also at increased risk of IPV even if they married as adults themselves 36.…”
Section: Resultsmentioning
confidence: 95%